Molecular Detection and Gene Expression of Some Adhesion-related Genes in Uropathogenic Escherichia coli in Clinical Isolates from Urinary Tract Infection Patients - Alaa Ali Jawad Mhannawee; Serdal Tarhane (Biomedical and Biotechnology Research Journal)
Background: Uropathogenic Escherichia coli (UPEC) strains encoding superficial and secretory virulence factors can colonize and facilitate bacterial growth in the host urinary tract, causing urinary tract infection (UTI). The current study seeks to gene detect and evaluate the expression of the alpha-hemolysin, fimbrial adhesion-related gene (fimH), nonfimbrial adhesion-related gene (tosA), and P adhesin gene (papG) genes in UPEC. Methods: Molecular methods were employed on bacteria isolated through polymerase chain reaction (PCR) amplification to assess the expression levels of these genes using reverse transcription quantitative PCR. The data were analyzed using the appropriate method. Results: The expression levels of the Hly A, Tos A, Fim H, and Pap G genes increased during UTIs. The highest expression was recorded for the Hly A gene at 44.341, followed by the Tos A gene at 24.115, Fim H at 20.272, and Pap G at 14.466, respectively. The study demonstrated that the Hly A, Tos A, Fim H, and Pap genes were expressed in UTIs caused by E. coli. Among these genes, the highest mean expression value was observed for the Hly A gene, followed by the Pap G, Tos A, and Fim H genes. In addition, the findings indicated that the female group exhibited higher rates of bacterial infections, particularly UTIs caused by E. coli, than the male group. Conclusions: This study concluded that there is a high prevalence of the virulence genes fimH and papG among E. coli isolates. This finding suggests that these genes play a crucial role in the development of UTIs. The results may help clarify the pathogenesis of UPEC and could lead to improved treatment strategies for patients with UTIs in this geographic area.